An assessment of the qualification of chef cook in selected restaurant in Makati City/ Rowena C. Andam, and Natassia D. Dellina. - Adam, Rowena C.; Dellina, Natassia D. (Parañaque City: Olivarez College, 2006)
Statement of Problem This study is an attempt to determine the qualifications for chef cooks among selected restaurant in Makati City To determine the above-mentioned qualifications of a chef, the following question were formulated: 1. How are chef cook hired? 2. What are the qualifications needed to qualify for this cook? 3. What are the different qualifying examinations given to a chef cook? Research Method This study will provide baseline information on the qualification for chef cooks selected restaurants. It will likewise benefit restaurant operators in Makati City, since they will be aware of the proper qualifications when hiring a chef cook. A significance for the student, department, college & industry. Subjects of the Study 1. Four (4) restaurants were in Makati selected the survey study. These Casa Armas, Chef d Angelo, Italianni's, Gerry's Grill. 2. Personal interviews and questionnaires. Is being used in gathering the needed data. Personal interview limits composed of the Operational Management of the establishment include in this survey. 3. Only the Operational Manager will be authorized to answer the questionnaire & only he will be the one answer the question being asked during the interview. Research Instrument Survey and documentary analysis were used as the main data gathering approach, and reinforce by in the interview on some operational manager of selected restaurant in Makati City. A. Conclusion Finding of the study the following: 1. That Chef cooks were mostly hired although promotion was done within the establishment. 2. That this type of recruitment was affective because some workers were already familiar with the operation and policies of the food service establishment. 3. That qualification needed to qualify for chief cook was a work experience of at least 5 years: physical fitness for the job not necessarily under fifty (50) of age: have the abilities to communicate in English and College graduate. 4. That examination given to a prospective applicant for chief cook included interviews, trade or skill test and physical examination. 5. That among problems related with the those recruitment of chief cooks were: scarcity of good cooks, those available lacked exposure/ training, difficulty to get good cooks because of long working hours: and low salary and management skills. B. Recommendation: With the above mentioned, finding, the researcher would like to the following recommendations: Filipinos cooks can compare with foreign cooks they could be given sufficient training or exposure. The Philippines can produce many good cooks if only this profession will be upgraded and professionalized like in Europe. Student taking up Hotel and Restaurant Management should be encouraged to train further in the culinary arts. Through apprenticeship and practicum training in noted Hotel kitchens. Likewise, those who are already engaged in this profession should take up management training to make them more effective and in- demand in the food service industry.
Undergraduate Thesis